Basaloid Squamous Cell Carcinoma of the Uterine Cervix - Imran, Ambereen A; Salaria, Sarosh Majeed (International Journal of Pathology, 2018)
AbstractBasaloid squamous cell carcinoma (BSCC) is a rare and highly aggressive variant of squamous cell carcinoma. Itwas first described by Wain et al in 1986. The characteristic histologic features are nests, groups, trabeculae andlobules of small basaloid cells with peripheral palisading. There may be areas of comedonecrosis. The tumor has, insome cases, been found to be associated with areas of typical squamous cell carcinoma. The most frequentlyinvolved sites are larynx, hypopharynx, tonsils and base of tongue. But other areas of the body like nose, paranasalsinuses, external ear, submandibular region, oesophagus, lung, uterine cervix, vulva, vagina and anus are reportedto be afflicted. A case of BSCC of uterine cervix was encountered and is being reported here.